2023
DOI: 10.1161/atvbaha.122.318015
|View full text |Cite
|
Sign up to set email alerts
|

CAPN1 (Calpain1)-Dependent Cleavage of STIM1 (Stromal Interaction Molecule 1) Results in an Enhanced SOCE (Store-Operated Calcium Entry) in Human Neonatal Platelets

Abstract: Background: Altered intracellular Ca 2+ homeostasis in neonatal platelets has been previously reported. This study aims to examine the changes in the Ca 2+ entry through the store-operated calcium entry (SOCE) mechanism in neonatal platelets. Methods: Human platelets from either control women, mothers, and neonates were isolated and, following, were fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Given that calcium is pumped in the AGs by the activity of SERCA3 and the acidic nature of these granules, we further analysed the possible alteration in the acidic nature of these granules using LysoSensor-green, a pH-sensitive dye that is directed to the acidic compartments and, thus, is widely used to stain lysosomes. [45][46][47] Our results demonstrated an alteration in neonatal platelet AGs as the amount of LysoSensor-green accumulated in these AGs was reduced in neonatal platelets compared with platelets from maternal and control women (see confocal images in Figure S3C; Blue: DTS stained with ER-Tracker, Green: AGs stained with LysoSensor-green). As a result, the subsequent addition of GPN to platelets caused a rapid reduction in LysoSensor-green fluorescence in maternal platelets; meanwhile, fluorescence in neonatal platelets unchanged (Figure S3B; Video S1).…”
Section: Altered Ca 2+ Release From Different Intracellular Ca 2+ Poo...mentioning
confidence: 62%
See 3 more Smart Citations
“…Given that calcium is pumped in the AGs by the activity of SERCA3 and the acidic nature of these granules, we further analysed the possible alteration in the acidic nature of these granules using LysoSensor-green, a pH-sensitive dye that is directed to the acidic compartments and, thus, is widely used to stain lysosomes. [45][46][47] Our results demonstrated an alteration in neonatal platelet AGs as the amount of LysoSensor-green accumulated in these AGs was reduced in neonatal platelets compared with platelets from maternal and control women (see confocal images in Figure S3C; Blue: DTS stained with ER-Tracker, Green: AGs stained with LysoSensor-green). As a result, the subsequent addition of GPN to platelets caused a rapid reduction in LysoSensor-green fluorescence in maternal platelets; meanwhile, fluorescence in neonatal platelets unchanged (Figure S3B; Video S1).…”
Section: Altered Ca 2+ Release From Different Intracellular Ca 2+ Poo...mentioning
confidence: 62%
“…As reported in the literature, TG at very low concentration (10 nM) depletes DTS from adult platelets because SERCA2b is found in DTS membranes; meanwhile, 20 μM of TBHQ blocks SERCA3 function and, subsequently, depletes Ca 2+ stored in the AGs, where the SERCA3 isoform has been localized. 24,45,46 As shown in Figure 2A, TBHQ (20 μM) was unable to mobilize Ca 2+ from AGs in neonatal platelets compared with platelets from maternal or control woman (p < 0.05, n = 4); similarly, Ca 2+ entry due to emptying of AGs was also significantly reduced by 80% ± 10% compared with adult platelets (p < 0.001; n = 2-4). In addition, preincubation of neonatal platelets for 5 min with TBHQ (20 μM) in a Ca 2+ -free HBS medium (100 μM of EGTA was added) and, subsequent, stimulation with Thr (0.1 U/mL) presented a significant reduction of 20% ± 8% in the Ca 2+ mobilization compared with adult platelets [p < 0.05; compare black-bars in the graph bars of the Figure 2B(…”
Section: Altered Ca 2+ Release From Different Intracellular Ca 2+ Poo...mentioning
confidence: 84%
See 2 more Smart Citations
“…5 Plenty of novel insights about platelet physiology, in particular regarding complex molecular dynamics and regulatory networks involving even ion homeostasis are being provided. 6 A physiological pathway that is currently matter of research involves the glycoprotein V, a platelet transmembrane protein which is proteolytically cleaved by thrombin during thrombus formation: it was recently shown that the soluble glycoprotein V released from platelet surface specifically reduces fibrin formation in vitro and in vivo and thereby may prevent occlusive thrombosis without causing hemostatic impairments. 7 Other recent studies found that shear-induced platelet aggregation (SIPA) is primarily involved in platelet activation and aggregation, because local shear stress generated by blood flow in obstructed vessels can be more than 3-fold higher compared with normal vessels.…”
mentioning
confidence: 99%